Tan Sri Dato Sri Abi Musa Asaari proclaimed as UMP Pro Chancellor - UMP, PNC (2019)
Tan Sri Dato’ Sri Abi Musa Asa’ari Mohamed Nor was proclaimed as Universiti Malaysia Pahang (UMP) Pro-Chancellor during the university’s 14th convocation that was graced by UMP Chancellor, His Royal Highness Seri Paduka Baginda Yang di-Pertuan Agong Al- Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah Ibni Almarhum Sultan Haji Ahmad Shah A-Musta’in Billah.